Effects of a fast growth microdiet on larval development of gilthead seabream (Sparus aurata, Linnaeus, 1758) and meagre (Argyrosomus regius, Asso, 1801) - Viegas, Sofia Isabel Martins (2017)
Dissertação de mestrado, Aquacultura e Pescas, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2017